1993
DOI: 10.1136/bjsm.27.3.186
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 6-week, 6 days per week, training on pituitary function in recreational athletes.

Abstract: The influence on pituitary function of 6 weeks of training on 6 days a week was examined in six recreational athletes. Endurance training on a bicycle ergometer for 31-33 min was performed on 4 days each week at 90-96% (weeks 1-3) and 89-92% (weeks 4-6) of the 4 mmol lactate thresholds determined on day 0 and day 21, respectively, with interval training of 3-5 x 3-5 min in addition on 2 days a week at 117-127% and 115-110%, respectively. Determination of the serum hormone levels and a combined pituitary functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
2
9

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 16 publications
4
41
2
9
Order By: Relevance
“…Similar findings can be found for all hypothalamopituitary-peripheral hormonal axes with a biphasic response to overload involving predominantly peripheral mechanisms in early phases of overload and of more central mechanisms in more prolonged phases of overload and overtraining (Lehmann et al 1993b(Lehmann et al , 1997. In reality, however, there is a more gradual change from the compensated to the decompensated phase of response.…”
Section: The Response To Training and Overtrainingsupporting
confidence: 67%
See 1 more Smart Citation
“…Similar findings can be found for all hypothalamopituitary-peripheral hormonal axes with a biphasic response to overload involving predominantly peripheral mechanisms in early phases of overload and of more central mechanisms in more prolonged phases of overload and overtraining (Lehmann et al 1993b(Lehmann et al , 1997. In reality, however, there is a more gradual change from the compensated to the decompensated phase of response.…”
Section: The Response To Training and Overtrainingsupporting
confidence: 67%
“…This is schematically drawn in Fig. 3 for the HPA axis (Barron et al 1985;Lehmann et al 1993b;Urhausen et al 1998;Wittert et al 1996).…”
Section: The Response To Training and Overtrainingmentioning
confidence: 99%
“…Serum cortisol at rest has been suggested to increase with heavy training (1,26) and overtraining (28), but it has also been found to decrease (21) and to be lower in elite than in good distance runners (6). In the present study there were both increases and decreases in serum cortisol at rest in each group.…”
Section: Mood Dynamicssupporting
confidence: 50%
“…in higher brain centres will certainly influence hypothalamic output (Lachuer et al 1994). Lehmann et al (1993a) introduced the concept, that hypothalamic function reflects the state of OR or the OTS because the hypothalamus integrates many of the stressors. It has been shown that acute stress not only increases hypothalamic monoamine release, but consequently corticotrophic releasing hormone (CRH) and adrenocorticotrophic hormone (ACTH) secretion (Shintani et al 1995).…”
Section: Assessment Of Overtrainingmentioning
confidence: 99%